The Communalization of Law Enforcement in India: Police Complicity, Impunity, and Anti-Muslim Violence - Bari, Mohammad Saiful (Tebuireng: Journal of Islamic Studies and Society, 2026)
Existing scholarship has documented police bias during episodes of anti-Muslim communal violence in India, despite there is a limited explanation for why similar patterns of police conduct recur across different political administrations and geographies. Thus, this study examines how sections of Indian police become complicit in communal violence through active participation or strategic neutrality. This study uses a qualitative comparative analysis of the 2002 Gujarat pogrom, the 2013 Muzaffarnagar riots, and the 2020 Northeast Delhi communal violence to identify recurring patterns of delayed police intervention, selective enforcement, partisan investigations, and post-violence impunity. Adopting the theoretical framework of Paul Brass’s institutionalised riot system, Veena Das’s concept of illegible state, Michel Foucault’s concept of governmentality, and Deana Heath’s genealogy of colonial policing, the study develops the concept of structural omission to explain why these patterns persist across different political and historical contexts. The study contributes to scholarship on communal violence, policing, and state accountability by relocating the explanation for police complicity from individual misconduct to institutional architecture.